Kajian Pemanfaatan Limbah Serbuk Kayu Mebel sebagai Media Tanam pada Mikrogreens Sawi (Brassica juncea L.): Study of the Utilization of Furniture Sawdust Waste as a Planting Medium for Mustard Greens (Brassica juncea L.) Microgreens - Winarto, Fahmi Romadani; Haryanta, Dwi; Herawati, Jajuk (Agrocentrum, 2025)
Conversion of agricultural land is becoming increasingly narrow, so microgreens have emerged as a solution for cultivating vegetables in limited space with high nutritional value. The aim is to explore the use of furniture sawdust waste as an alternative growing medium to increase growth and nutritional content, especially beta carotene, in mustard greens. This research uses different treatment methods for planting media and nutrient concentrations. The research results showed that treatment with nutrient concentration E (ecoenzyme) could increase the beta carotene content in mustard green microgreens. Data analysis showed that there was a real interaction between E0 and E1 treatments, with beta carotene levels increasing 2-fold from 3.65 mg to 21.05 mg. Research Contribution This research is expected to contribute to the development of sustainable agricultural technology and provide information for business actors about the use of waste as an economical and environmentally friendly planting medium. This research succeeded in showing that furniture sawdust waste can be used as an effective planting medium to increase the beta carotene content in mustard greens. Treatment with nutrient concentration E (ecoenzyme) showed significant results with an increase in beta carotene levels up to 2 times. This research contributes to the development of sustainable agricultural technology and the use of waste in an economical and environmentally friendly manner.